Application of Social and Emotional Skills to Develop Students' Scientific Attitudes in Science Learning in Grade VI of Islamic Elementary Schools: Penerapan Sosial Emosional Skill untuk Mengembangkan Sikap Ilmiah Siswa dalam Pembelajaran IPAS Kelas VI Madrasah Ibtidaiyah - Silma Indana Zulfa; Eva Luthfi Fakhru Ahsani (Madrosatuna: Journal of Islamic Elementary School, 2026)
This research is motivated by the fact that many students are not actively involved in learning, are lazy to ask questions, receive information without questioning the source or process, and lack responsibility and discipline in doing assignments. The purpose of this study is to describe the process of implementing the Social Emotional Skill approach, describe students' scientific attitudes with the application of the Social Emotional Skill approach, and analyze students' responses to the application of the Social Emotional Skill approach to develop scientific attitudes. This study uses a descriptive qualitative approach with subjects of grade VI MI NU Miftahul Ulum Loram Kulon Jati Kudus. Data were collected through observation and questionnaires, then analyzed including data reduction, data presentation, and drawing conclusions. The results of the study show that this approach consists of three stages: planning, implementation, and evaluation. There are positive changes in students' scientific attitudes in learning. Student responses show very good scores in the application of the Social Emotional Skill approach. This study concludes that the application of the Social Emotional Skill approach in science learning is proven to be effective in facilitating the development of students' scientific attitudes as a whole.